Ground beef patties prepared from brisket, flank and plate have unique fatty acid and sensory characteristics. (May 2015) - Blackmon, Terronica; Miller, Rhonda K.; Kerth, Chris; Smith, Stephen B.
Abstract: We hypothesized that unique ground beef products could be formulated from brisket, flank, and plate primals. Primals were taken from 4 USDA Select carcasses from conventionally produced cattle, selected at random in a commercial packing plant. Lean and fat trims were separated, and ground beef was formulated from each primal to contain 10, 20, or 30% total fat. Brisket patties contained higher proportions of monounsaturated fatty acids and less saturated fatty acids than flank patties. There were no differences in n − 6 or n − 3 fatty acids across primal type or fat level. After cooking, brisket patties had higher bloody/serumy and fat-like descriptor values than flank patties. Plate patties generated higher amounts of lipid-derived volatiles than patties from the brisket or flank. Brisket patties generally had higher amounts of pleasant headspace volatiles whereas the plate relied more heavily on Maillard-derived volatiles than flank patties. We conclude that individual primals can be used to formulate ground beef with unique compositional and flavor characteristics. Highlights: Ground beef was formulated from brisket, flank, and plate primals. Brisket patties contained more monounsaturated fatty acids than flank patties. Brisket patties had more pleasant headspace volatiles than flank patties.